Industrial development environment and innovation efficiency of high-tech industry: analysis based on the framework of innovation systems. Issue 4 (3rd April 2018) - Liu, Zhiying; Chen, Xiafei; Chu, Junfei; Zhu, Qingyuan
ABSTRACT: This present paper studies the relationship between the industrial development environment (IDE) and the innovation efficiency (IE) of China's high-tech industry. First, drawing upon insights from research on regional innovation systems and sectoral innovation systems, the paper proposes a definition of the IDE within which China's high-tech industry exists. Then, by a factorial analysis, three main components reflecting the IDE are obtained: regional development conditions, regional consumption potential, and interactions between innovation actors. Furthermore, the impacts of various facets of the IDE on three kinds of IE are investigated through the DEA-Tobit regression approach. Based on the results, our analysis can provide information for policymakers to create a favourable environment for China's high-tech industry.